Determinant of Stunting in Indonesia: A Review Article - Indah Budiastutik; Sri Achadi Nugraheni (Universitas Ahmad Dahlan, 2018)
Background: Stunting prevalence data in Indonesia has sufficient number relatively similar with riskesdas result year 2007 (36.8%), 2010 (35.6%) until 2013 increase to 37.2% (1), although riskesdas 2018 result decline 6.4%. It becomes 30.8% (2), but the problem of stunting in Indonesia is still above prevalence globally, 22.2% (3). WHO determines definition of nutrition case is fewer than 20% (4), therefore Indonesia included to state which has public health problem, especially stunting case. Stunting has long risk such as PTM when going adult, though it can be prevented early.Objective: this article review aims to identify determinant factors which take a risk to stunting of Indonesian children.Methodology: We applies concept framework from WHO about stunting on children. By using designs of non-randomized control trials, observational studies, this article review applied through browsing the article using Google scholer, Proquest, Medline and several on line journals which published 10 years latest, then taking research subject of mother and child, Research applied in West Kalimantan.Result: From browsing finding obtained 2.435 relevant articles to conduct the citation, there are 2.122 completed the requirement after conducting the title and absract review, after carrying out the screening throuh full text review of articles obtained 360 titles, then 15 articles which completed the inclusive/ exclusive criteria. Based on literature finding of review consistently shows that giving inclusive mother‘s milk, low economic status of household, premature birthing, length of birthing and low education of mother, and also children live in the village, bad sanitation, and the culture is a determinant factor of children stunting in Indonesia.Conclusion: From the comprehensive synthesis concerning stunting on Indonesian children can be found out who is the most susceptible of stunting and the factors influence of stunting on children.